Application of Range of Motion Exercises to Increase Muscle Strength in Non-Hemorrhagic Stroke Patients - Adirson Barbosa De Oliveira; Abdul Muhith; Siti Nur Hasina (Indonesian Journal of Global Health Research, 2025)
Stroke is a disruption of blood flow in the brain, patients who suffer from weakness in the limbs can cause a decrease in muscle strength, so they cannot move their body. Solutions to prevent and reduce disability, complications and death after having a stroke. Rehabilitation in stroke patients one of them is by doing Range of Motion exercises. Objective: This study was to analyze the application of ROM exercise to increase muscle strength in ischemic stroke patients. Design: This study used quasi-experimental with Pre-Test and Post-Test approaches with a sample of 15 people using Purposive Sampling techniques. Data analysis using the Wilcoxon Match Pairs test. The data collected consisted of respondents' characteristics in the form of age, gender, history of stroke and muscle strength. The instrument used is an observation sheet and muscle strength measurement, MMT (Manual Muscle Testing). Results: Showed that there was an increase in muscle strength after (post-test) intervening with an average value of 4,13, while muscle strength up to condition 5 (normal) after implementing as many as 7 people (40,67%).